The The dynamic process of student-teachers’ construction of identity as future teachers - Torres Cepeda, Nancy Maria; Ramos Holguín, Bertha (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper reports the findings of a qualitative narrative-inquiry study aimed at exploring what English-as-a-Foreign-Language (EFL) student-teachers’ life stories revealed about their identity construction as future teachers. The project was carried out among eighth-semester student-teachers from a public university in Tunja, Boyaca (Colombia). Hence, the data collection drew upon written life stories and in-depth interviews. Findings suggest that there are some critical factors that helped student-teachers construct their identities as future EFL teachers. These factors are all tied to previous experiences of student-teachers as language learners themselves, a connection and affiliation they establish with their teacher educators as projected images they have of themselves as future teachers. Moreover, real teaching experiences were opportunities for student-teachers to make sense of the myriad issues education involves, which made them, develop positions towards education as future teachers.